METHODOLOGICAL IMPROVEMENT OF PLURICULTURAL COMPETENCE FORMATION IN FUTURE PHILOLOGISTS: INTEGRATING COGNITIVE, AFFECTIVE, AND CULTURAL DIMENSIONS ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2025)
This article explores the methodological improvement of pluricultural competence formation in future philologists through the integration of cognitive, affective, and cultural dimensions. It argues that pluricultural competence encompassing awareness, empathy, and adaptability requires a holistic pedagogical approach combining intellectual understanding, emotional engagement, and intercultural behavior.